Estudio de factibilidad para la creación de una empresa proveedora de bienes y servicios para las motonaves que llegan al puerto de Buenaventura (2015)
The business proposal presented below is conducting a feasibility study for setting up a business for goods and services for motor vessels arriving at the port of Buenaventura, the general objective that will achieve at certain stages of the project, as they are doing studies such as technical, market and financial analysis which shows that the application of this model is feasible. When the process of observation and previous research is that; invest in a company that provides supply and supply vessels arriving at the port of Buenaventura, is profitable. This being a solid proposal characterized by high demand and low bidders in the city. Likewise, it is worth noting that having few companies providing this service (oligopoly), proves to be a profitable investment proposal, generating jobs and sustainable with a dynamic and innovative way to meet the needs of customers. It is concluded that despite the mistakes with some proposals to offer services for vessels that are not of primary need, other offerings such as providing the vessel and supplies such as power, telecommunications, guides and translators, and services in general. It is likely that the company has a stable financial development garcias that in a short period of two years maximum investment amount would recover and gives a gain of 148%